Compromised Peacebuilding4. Issue 3 (18th June 2014) - Barnett, Michael; Fang, Songying; Zürcher, Christoph
Abstract : There is considerable evidence that peacebuilding operations are more likely to reproduce important elements of the status quo than they are to propel post‐conflict states toward a liberal democracy. In contrast to existing theories that focus on the resources available to peacebuilders or the degree of damage caused by the war to explain the outcome, we highlight the interaction between international and domestic actors. Specifically, we conceive of peacebuilding as a strategic process involving peacebuilders, a postwar government, and other local elites. The equilibrium results show that this process typically concludes in a compromised peacebuilding outcome. This is not surprising when the policy preferences of the actors diverge, but the results also hold when domestic elites prefer a liberal democracy to the status quo. Why? Primarily, because postwar governments are rewarded by relatively impatient peacebuilders with more resources than they would otherwise receive. Additionally, if there exists a secondary elite with veto power, a compromised outcome becomes even more likely. We illustrate these findings with reference to post‐1989 peacebuilding operations. Although peacebuilding might not work as it is intended, in the conclusion, we argue that it is better than the alternatives and propose a more realistic measure of peacebuilding success.